THE MAGNITUDE AND PATTERN OF CS DELIVERIES IN AA PRIVATE HEALTH CARE FACILITIES - Negussie, Dr. Dereje; E., Mesfin; G/Y, Asfawessen; T., Mesfin (Ethiopian Journal of Reproductive Health, 2020)
Abstract Background: In Ethiopia, the national CS rate stands at 3.79% nationally currently, which is significantly below the World Health Organization (WHO) recommended rate of 10-15%, signifying barriers in access. However, CS rates in private facilities in Addis Ababa currently stand at 41%. Objective: To assess the magnitude of CS deliveries, indications, and factors associated with CS delivery in private health facilities in Addis Ababa. Methods: This is a retrospective, descriptive, cross-sectional study on magnitude, indications and associated factors of CS delivery from 24 private facilities in Addis Ababa. Results: The study found a CS rate of 57.3%. CS was highest amongst age group (25-29 years) 42.0%, primiparous (35.0%) and at GA of 37-42(84.0%) weeks. And majority were primary CS 253(55.0%) the three most common indications were NRFHR (14.6%), maternal request, (10.8%), and breech presentation (8.8%). And the mean CS procedure and 48 hrs hospital cost were 4,905.00 and 14,657.00 ETB respectively. Conclusion and recommendations: We have documented higher CS rate. The rates were higher amongst relatively young age group and primiparous. Indications as previous CS, non-reassuring fetal heart rate, and client request were the commonest. The reasons behind the high CS rate are likely a combination of provider behavior and incentives, social and cultural factors affecting the mothers’ decision. We recommend the conduct of further studies to uncover and address the causes the high CS rates. Key words: CS rate, private facilities, Addis Ababa.